Trigeminal neuralgia secondary to meningioma of petroclival localization - Jurjević, Ante, liječnik (Array, 2009)
Abstract: Trigeminal neuralgia is characterized by paroxysmal episodes of facial pain in the distribution of the trigeminal nerve. It can occur in either sex but is most frequently seen in women aged 50–60 years. This article presents case of trigeminal neuralgia in a 55-year-old female patient caused by meningioma of petroclival localization. The article underscores the importance of neurologic and neuroradiologic examination in diagnosing and managing patients with facial pain conditions